IMPACT OF GREEN LEADERSHIP ON SCHOOL ENVIRONMENT AT HIGHER SECONDARY LEVEL - Sammar Fatima; Dr. Muhammad Aamir Hashmi; Talha Ahmed Salam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
This quantitative study was conducted to find the use of leadership techniques by higher secondary schools of district Lahore. The population of the study was the Secondary school teachers of publicschools.95 principals and 380 Secondary school teachers were selected as a sample through convenient sampling for data collection. A questionnaire was used for data collection. Descriptive statistics (t-test) were used to analyze data. To assess the use of different leadership techniques by Secondary school heads and teachers mean and standard deviation was identified According to the results the most common leadership strategies were: offering prayers, discussing stress with family, friends and seniors, leaving everything on Allah, watching TV, future planning to avoid stress and sleeping. And the strategies that were not common; taking exercise, deep breathing, weeping, consulting with relatives, and finding own mistake, diary writing, movie watching and consultation with specialist etc. On the basis of these results recommendations were made.